Experimental studies of the process of grain transportation by the elevator of grain combine harvester - Burlaka , A. A.; Yakhin , S. V.; Dudnyk, V. V. (Scientific Progress & Innovations, 2019)
The purpose of this study is to substantiate the method of monitoring the parameters of grain stream flow of various crops in the scraper elevator of a grain combine harvester using an improved capacitive-wave type sensor. Methods of the research. The primary data of experimental studies, obtained with the help of a specially developed device, have been processed using mathematical and statistical analysis methods. The research results. The quality of grain transportation by scraper elevators used on combine harvesters and in transportation lines of grain processing enterprises does not meet modern requirements – there is incomplete unloading, grain crushing by scrapers, chain and sprockets of the elevator. The operating conditions of the combine grain transportation system while threshing low-yield crops with a significant advantage of non-cereal part in the yield were not taken into account. Studying the characteristics of grain flow during transportation and unloading by the scraper elevator, we have improved and used the experimental installation, which was additionally equipped with a system for monitoring the intensity of transportation. In the course of experimental studies, the reflection of the flow intensity was studied depending on the elevator production performance and transportation speed. We used multiple linear regression to describe the dependence of reflecting the intensity of the flow for each type of crop. According to the results of the experiments, the intensity of the grain flow can be considered as the degree of loading the scraper elevator relative to the nominal value. In the transport systems of grain processing machines, such intensity is almost always nominal, and on grain combine harvesters there is a partial incomplete loading due to diverse harvesting conditions. The elements of scientific novelty. The experimental installation has been improved and used in our research as an object of intellectual property, protected by patents for invention and patents for a useful model. The method of studying technological processes of grain transportation by elevator also has patent protection. The latter one confirms the scientific novelty of this publication. Practical importance. The results of the research have been used to improve the grain transportation line of the KZS-9-1 "Slavutych" combine harvester and they are significant for further optimization of grain transportation modes with similar scraper elevators.